THE EFFECT OF CAPITAL EXPENDITURE AND ECONOMIC GROWTH ON THE HUMAN DEVELOPMENT INDEX OF THE DISTRICT CITY IN NORTH SUMATERA - Rinaldi, Muammar; Arifin, Zainal; Maipita, Indra; Hutasuhut, Saidun (Advances in Social Sciences Research Journal, 2020)
This study aims to analyze the effect of capital expenditure and economic growth simultaneously on the Human Development Index (HDI) in districts/cities in North Sumatra. This type of research is a descriptive-quantitative approach that suppresses its analysis of numerical data that is processed by the statistical method. Sources of data in this study were taken from the Central Bureau of Statistics of North Sumatra for the HDI data. The sample in this study is all districts/cities in North Sumatra for the period 2013-2017. The data analysis technique used in this study uses panel data regression with Eviews 7 because, in this study, there are characteristics of cross-section and time-series data simultaneously. The results of this study indicate that capital expenditure partially has a positive and significant effect on the Human Development Index in districts/cities in North Sumatra. Economic growth partially has a positive and significant effect on the HDI in districts/cities in North Sumatra, and capital expenditure and economic growth have a positive and significant effect simultaneously on the Human Development Index in districts/cities in North Sumatra.